Causes and determinants of blindness in inmates of blind schools - Gupta, Vivek; Agrawal, V. K. (International Journal Of Community Medicine And Public Health, 2021)
Background: Globally visual impairment is a serious public health, social and economic problem, 1.1 billion people are visually disabled. India has 12 million blind people. Studies conducted so far have highlighted mainly the medical aspects of blindness. With the intention to study medico-social aspects of blindness in India the current study was undertaken in two institutes for the blind in Pune. Methods: It was a cross sectional descriptive study conducted using a study questionnaire. A modified WHO eye examination record for blindness and low vision was administered to all (290) inmates of Technical Training Institute of Pune Blind Men’s Association and The Pune School and Home for the Blind Boys from 01 Aug 2014 to 31 July 2015 at Pune. Psychosocial aspects of inmates were recorded as per hospital anxiety and depression scale (HADS). Analysis of collected data was done with the help of epi info and PEPI Programs version-4. Results: Retina (61.7 percent) and cornea (31.0 percent) were the main site of lesion. Overall, 40.4 percent had potentially avoidable cause of blindness. 46.6 percent of inmates had normal psychosocial patterns as per HADS scale. Conclusions: Strengthening of preventive and curative services for the complex medico-social aspects of blindness. Involvement of retina in 61.7 percent of inmates shows that genetically determined diseases are an emerging important cause of blindness justifies the requirement of genetic counselling along with other preventive and curative intervention for prevention of blindness in India.